2018
DOI: 10.17219/acem/69708
|View full text |Cite
|
Sign up to set email alerts
|

Benign paroxysmal positional vertigo in patients after mild traumatic brain injury

Abstract: Benign paroxysmal positional vertigo should be diagnosed and treated successfully in patients after head trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 19 publications
2
19
0
Order By: Relevance
“…This is in accordance with Ahn et al and Davies et al who have reported an incidence of 23% and 25% respectively [5]However, others have documented a lower incidence varying from 8.5% to 17% [7,10,12,13]. The commonest age group affected was 31-50 years group(44.4%) which is in agreement with Jozefowicz Korczynska et al and Haripriya et al [14,13].Males predominated in our cohort(55.6%). Similar observations have been made by others [14,13].…”
Section: Discussionsupporting
confidence: 93%
“…This is in accordance with Ahn et al and Davies et al who have reported an incidence of 23% and 25% respectively [5]However, others have documented a lower incidence varying from 8.5% to 17% [7,10,12,13]. The commonest age group affected was 31-50 years group(44.4%) which is in agreement with Jozefowicz Korczynska et al and Haripriya et al [14,13].Males predominated in our cohort(55.6%). Similar observations have been made by others [14,13].…”
Section: Discussionsupporting
confidence: 93%
“…Thus, these results again indicate a very large variation in the population of patients studied. In addition, Fife and Kalra [28], however, emphasize that the absence of disturbances detected in VNG test does not exclude the peripheral cause of ailments that may be related to abnormalities of the utricle and sacculus in patients after brain injury, which was presented in another publication [9]. In the present study, the compensation and normalization of the VNG records occurred in almost 40% of the patients after 6 months, while the central disorders were significantly more frequently identified in the remaining patients.…”
Section: Discussionmentioning
confidence: 99%
“…'Post-traumatic dizziness/vertigo' is a term that indicates a common etiology for a very heterogeneous presentation of peripheral and central vestibular system dysfunction. Patients with benign positional paroxysmal vertigo (BBPV) as a result of a traumatic event constitute a different diagnostic and treatment group [9][10][11]. In literature, there are quite divergent data on the incidence of imbalance and dizziness after head traumas.…”
Section: Introductionmentioning
confidence: 99%
“…It is important first to evaluate if no concern related to cervical spine is present, before the administration. It is also termed the "headhanging positioning maneuver" [35].…”
Section: Dix-hallpike Maneuvermentioning
confidence: 99%
“…The patient's head is held in this position and the clinician verify the eyes to detect or not the presence of nystagmus. To complete the maneuver, the patient is returned to the seated position and they eyes are observed to detect presence of reversal nystagmus [35,36].…”
Section: Dix-hallpike Maneuvermentioning
confidence: 99%